Exploring Students’ Experiences in Project-Based Learning in the Economics Education Program at Jambi University - Tia Ramda Sari; Vinda Afnita (Jurnal Pendidikan Ekonomi, 2025)
This study aims to explore students’ experiences in the implementation of Project-Based Learning (PjBL) in the Economics Education Study Program at the University of Jambi. Using a descriptive qualitative method, this research investigates students’ direct experiences through interviews, observations, and project documentation analysis. The findings show that students engaged in PjBL gain broader learning opportunities and experiences that foster creativity, encourage active participation, and enhance collaboration, critical thinking, and problem-solving skills. The study also reveals several challenges in PjBL, including unequal contributions among group members, limited time, coordination difficulties within groups, and insufficient learning resources, all of which may affect the quality of the projects produced, as well as the need for more intensive guidance from lecturers. The implementation of PjBL is influenced by lecturer readiness, student abilities, institutional support, and careful planning.